Forschungs- und Entwicklungsaktivitäten in der Potenzialschätzung berücksichtigen; Consider research and development activities in the potential assessment - Torsten Schmidt (Wirtschaftsdienst, 2022)
– Potential output is a measure of the longer-term production possibilities of an economy. Since this quantity cannot be observed directly, it must be determined on the basis of assumptions from existing data. The use of a production function was established in the European Commission's procedure for calculating potential output. However, it is important to capture all drivers of economic growth. In the current EU procedure, total factor productivity (TFP), which is interpreted as a measure of technological progress, is assumed to be exogenous. This means that key drivers of economic growth, in particular research and development (R&D) activities, are not explicitly taken into account. An extension of the production function approach can be derived from the theory of endogenous growth. This would improve the theoretical basis of the potential output estimates.
Keywords: C10; E60; O40; 330